Daily Versus Weekly Iron and Folic Acid Supplementation Regimen- A Randomized Parallel Open Label Trial among Reproductive Age Group Women in an Urban Poor Locality of Bengaluru - Vairavasolai P; Jayanthi Srikanth; Madhusudan M (Indian Association of Preventive and Social Medicine, 2020)
Introduction:The global prevalence of anaemia in non-pregnant women is 30.2% and in India it is 56.2%.At least half the burden of anaemia is associated with iron deficiency. Women of reproductive age are at higher risk of developing iron deficiency because of losses during menstruation. Though Daily supplementation with iron and folic acid for a period of 3 months has been the standard as an approach for the prevention and treatment of iron deficiency anaemia among women of reproductive age, there has been limited success with the daily regimen in public health programmes, Intermittent use of oral iron supplements has been proposed as an effective alternative. Objectives: To compare the effectiveness of weekly and daily oral iron and folic acid therapy in improving the Hemoglobin levels among the reproductive age group women, adverse effects and compliance to both the regimens. Method:This was a comparative Randomized parallel open label trial conducted in an urban poor locality of Bengaluru conducted between January 2014 and January 2016. All the women in the reproductive age group (15-45 years) with mild to moderate anemia were included in the study. Sample size of 106 subjects was randomly allocated into the 2 groups (53 into weekly regimen and 53 into daily regimen). The subjects were supplemented with IFA tablets for 3 months according to their regimen. Results:Mean increase in Haemoglobin (Hb) in the daily group (1.92±1.1 g/dl) was significantly (P=<0.01) more when compared to that in the weekly group (0.91±0.82 g/dl). Incidence of all the Adverse Drug Reactions (ADRs) were more in the daily group compared to weekly group. However, the difference was only significant for abdominal pain and metallic taste (P=<0.01 and 0.02 respectively). The proportion of subjects reporting at least one ADR was also significantly more (P=<0.01) in the daily group compared to the weekly group. Compliance for weekly regimen (97.12%) was found to be significantly better(P=<0.01) when compared to that of the daily regimen (94.07%). Conclusions: Daily regimen was more effective in raising the hemoglobin levels when compared to weekly regimen. Incidence of abdominal pain and metallic taste were significantly more in the daily group compared to weekly group. Compliance for weekly regimen was significantly better when compared to that of the daily regimen.